Eksplorasi Warisan Budaya Melayu: Seni, Kuliner, dan Festival yang Menyatu di Masyarakat - Elmustian Elmustian; Viona Julya Marsha; Elisia Elisia; Nasya Aprilia Fitri; Naila Amri; Helicya Fitriani; Surya Darma; Winda Triski (Sinar Dunia: Jurnal Riset Sosial Humaniora dan Ilmu Pendidikan, 2024)
The cultural heritage of the Malay community encompasses various significant aspects that reflect its richness, values, and identity, from social systems to festivals celebrating tradition. The Malay community is known for its egalitarian approach, evident in their language, social interactions, and open markets where nobles and commoners could mingle freely. Traditional arts and crafts, performing arts, and cuisine showcase the unique and rich cultural heritage passed down through generations. Pulau Penyengat, as a cultural and historical symbol, holds deep historical significance with landmarks like the Sultan Riau Grand Mosque and literary works by Raja Ali Haji, demonstrating its role in the spread of religion and culture. Events such as the Malay Cultural Festival and the Lampu Colok Festival play crucial roles in strengthening social bonds and introducing Malay culture to a wider audience. Preserving these elements is essential not only to maintain identity but also to inspire future generations to continue the traditions and noble values of the nation.